2015
DOI: 10.1111/gwat.12317
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality Modeling with a Small Data Set

Abstract: Seventeen groundwater quality variables collected during an 8-year period (2006 to 2013) in Andimeshk, Iran, were used to implement an artificial neural network (NN) with the purpose of constructing a water quality index (WQI). The method leading to the WQI avoids instabilities and overparameterization, two problems common when working with relatively small data sets. The groundwater quality variables used to construct the WQI were selected based on principal component analysis (PCA) by which the number of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…ANNs models the approximation and details component from the discrete wavelet transformation (see Figure 4). Dimensionality reduction methods such as PCA can reduce the dimension of the input data space to prevent redundancy [73]. Then, ANNs models some aggregative indices obtained by PCA (see Figure 4).…”
Section: Hybrid Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…ANNs models the approximation and details component from the discrete wavelet transformation (see Figure 4). Dimensionality reduction methods such as PCA can reduce the dimension of the input data space to prevent redundancy [73]. Then, ANNs models some aggregative indices obtained by PCA (see Figure 4).…”
Section: Hybrid Architecturesmentioning
confidence: 99%
“…Results showed that the hybrid model, namely chaos theory-PCA-ANN, had high prediction accuracy. Sakizadeh et al [73] applied early stopping which is fit for small networks and datasets to determine the model structure.…”
Section: Artificial Neural Network Models For Water Quality Predictionmentioning
confidence: 99%
“…Classification is a supervised learning process. [13][14][15][16][17][18][19][20][21][22][23][24][25]. Actually, the ANN models can handle crisp data, but some of the classification problems need to process the data with uncertainty along with the crisp data.…”
Section: Applications Of Ann and Fuzzy Logic In Groundwater Classificationmentioning
confidence: 99%